KARAKTERISTIK BAHASA REMAJA: KASUS RUBRIK REMAJA “DETEKSI” DALAM HARIAN JAWA POS - Foriyani Subiyatningsih (Humaniora, 2007)
Teenage language is a variant of bahasa Indonesia (bI) which is spoken by teenagers as a means of communication in their daily social interaction. Based on its characteristics, this variant of language belongs to the informal variation. Nevertheless, teenage language is characteristically different from the formal and informal bI in general. The linguistic characteristics of teenage variant include phonological, morphological, syntactical, and lexical characteristics.